PENGARUH LINGKUNGAN SEKOLAH DAN PERAN GURU TERHADAP MOTIVASI BELAJAR SISWA KELAS X PROGRAM KEAHLIAN OTOMATISASI DAN TATA KELOLA PERKANTORAN PADA MATA PELAJARAN PRODUKTIF DI SMK NASIONAL BANDUNG - Fani Cintia Dewi, - (2019)
Focus of the problem in this study was student's poor motivation. The aim of this study was finding out whether school environment and teacher's role play important role towards students' learning motivation. The method used in this study was explanation survey. This study was using quantitative study. The technique used in this study was multiple regression analysis environment was in the quite complex category, teacher's role was in the quite effective category and learning motivation was in the average category. Hypothesis testing shows that school environment and teacher's role have positive significant impact towards learning motivation.. Based on the study results of the analysis, students' perception toward school Keywords: School Environment, Teacher's Role, and Learning Motivation